"Don't Close the Door on Them": Recruiting and retaining vulnerable Black adolescents in prevention research. Issue 5 (3rd May 2021) - Powell, Terrinieka W.; Willis, Kalai; Smith, Bianca; Lewis, Quiana; Offiong, Asari
Abstract: There is a need to understand why some strategies work better than others for engaging vulnerable Black adolescents in prevention research, especially those who are affected by parental drug use. The current study sought to fill this gap. Thirty in‐depth interviews were conducted with parents who reported a history of illicit drug use ( N = 11), young adults who had a biological parent with a history of illicit drug use ( N = 14), and service providers who work with families affected by illicit drug use ( N = 5). Nearly all participants were Black and lived or worked in Baltimore, Maryland. Over half of the participants were female (62%). Interviews were recorded and ranged from 30 to 92 minutes in length. Data were analyzed using an inductive, content analysis approach. Four themes emerged (coined STAR): SAFE people and places minimize retraumatization; TEAMING UP with community partners increases acceptability; ADDRESSING a range of needs helps adolescents survive; and RELATABLE facilitators understand and listen to adolescents. Findings build onto and extend previous research that highlights strategies to recruit and retain vulnerable Black adolescents in prevention research.